Hubungan Kadar Hormon Estradiol 17-B dan Tebal Endometrium Uterus Mencit (Mus musculus l.) selama Satu Siklus Estrus - Sitasiwi, Agung Janika (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2008)
Research about animal reproduction can be observed from many aspects, i.e. oestrous cycle. The oestrouscycle is the manifestation of reproduction hormones changes, especially oestradiol 17- B. The oestradiol 17- B hormones causes changes of tissues structures of reproductive tracts. This research have been done toanalyze the correlation between changes of oestradiol 17- B hormones and uterine endometrial thicknessalong the oestrous cycles. The adult female Swiss Webster mice were used as laboratory animal. The phaseof oestrous cycle determined by vaginal smears. Blood and uterine samples collected in each oestrousphases. Hormones concentration counted with RIA, the thickness of endometrial determined on uterinehistological slides with paraffin methods and stained with HE. This search showed that a positivecorrelation between oestradiol 17- B hormones and uterine endometrial thickness along the oestrous cycle.It also showed that oestradiol 17- B hormones have a proliferative effects on reproductive tissues.